Post-error Slowing Reflects the Joint Impact of Adaptive and Maladaptive Processes During Decision Making - Fievez, Fanny; Derosiere, Gerard; Verbruggen, Frederick; Duque, Julie (Frontiers in Human Neuroscience, 2022)
Errors and their consequences are typically studied by investigating changes in decision speed and accuracy in trials that follow an error, commonly referred to as “post-error adjustments”. Many studies have reported that subjects slow down following an error, a phenomenon called “post-error slowing” (PES). However, the functional significance of PES is still a matter of debate as it is not always adaptive. That is, it is not always associated with a gain in performance and can even occur with a decline in accuracy. Here, we hypothesized that the nature of PES is influenced by one’s speed-accuracy tradeoff policy, which determines the overall level of choice accuracy in the task at hand. To test this hypothesis, we investigated post-error adjustments in subjects performing the same task while they were required to either emphasize speed (low accuracy) or cautiousness (high accuracy) in two distinct contexts (hasty and cautious contexts, respectively) experienced on separate days. Accordingly, our data indicate that post-error adjustments varied according to the context in which subjects performed the task, with PES being solely significant in the hasty context. In addition, we only observed a gain in performance after errors in a specific trial type, suggesting that post-error adjustments depend on a complex combination of processes that affect the speed of ensuing actions as well as the degree to which such PES comes with a gain in performance.